FRI0109 Influence of Aromatase Inhibitors Therapy on The Occurrence of Rheumatoid Arthritis in Women with Breast Cancer. Results from A Large Population Based Study of The Italian Society for Rheumatology. (15th July 2016) - Caprioli, M.; Carrara, G.; Pennetta, S.; Scirè, C.A.; ,
Abstract : Background: Though aromatase inhibitors (AIs) and tamoxifen are an essential part of estrogen receptor-positive breast cancer therapy, many patients discontinue the treatment for musculoskeletal symptoms [1]. Whether the musculoskeletal symptoms can be attributed to an underlying rheumatologic disease remain unknown. Sporadic case reports have described the onset of rheumatoid arthritis (RA) in patients who started therapy with tamoxifen or AIs [2]. Objectives: The purpose of this study was to evaluate the risk of developing rheumatoid arthritis (RA) in the population of patients with breast cancer treated with AIs. Methods: Data were collected from the administrative health-care database of Lombardy Region, Italy, from 2004 to 2013. This study follows a nested case-cohort design, including women with diagnosis of breast cancer (ICD9-CM codes 174) starting treatment tamoxifen, anastrozole, exemestane or letrozole. Level of neoplasia was defined according to relevant ICD9-CM codes as localized, node-positive, metastatic, unspecified. The risk of RA related to the prescription of the different drugs was estimated by survival models for competing risks and the results are presented as hazard ratios (HRs) and 95% confidence interval (95% CI), adjusted for age and disease duration. Interaction with age and time varying effects were also explored. Results: Out of a total of 10493 women with breast cancer with a median (IQR) age of 66 (57–74), 7533 (71.8%) started an active treatment with adjuvant endocrine therapy. In this subgroup of patients a total of 113 new cases of RA developed during the 26105.9 person-year of 10186 exposure periods, including time varying exposures in the same patient. Using tamoxifen as reference category, AIs therapy was associated with an increased risk of RA [adjusted HR 1.62 (95%1.03–2.56)], in particular due to anastrozole, even after adjusting for age and level of neoplasia (Table). Interaction with age was not statistically significant, and no time varying effects were observed. Conclusions: In a large population-based sample of women with breast cancer, the exposure to AI therapy compared with tamoxifen is associated with a significantly increased risk of developing RA, which is not influenced by the cancer severity and the relationship of age with indication to specific drugs. In patients with breast cancer treated with AIs and presenting arthralgia referral to rheumatologist is useful to exclude the onset of rheumatoid arthritis. References: Din OS, et al. Breast Cancer Res Treat 2010;120:525–38. Bertolini E, et al. Jt Bone Spine Rev Rhum 2011;78:62–4. Disclosure of Interest: None declared